EMPOWERING LEADERSHIP DAN PERAN INTRINSIC MOTIVATION SEBAGAI VARIABEL MEDIASI DALAM UPAYA MENINGKATKAN EMPLOYEE CREATIVITY - Roellyanti, Maria Valeria (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2015)
AbstractThe study was aimed to examine the effect of Empowering Leadership on Employee Creativity of BPD of Yogyakarta. This study was conducted considering four factors of Empowering Leadership, i.e. Enhancing the meaningfulness of work, Fostering participation in decision making, Expressing confidence in high performance, Providing autonomy from bureaucratic constraints and it was found that the combined effect of these factors influence Employee Creativity. In the other hand this study was aimed to know the role of Intrinsic Motivation as an moderation variable will effect to boost the Employee Creativity. The four dimensions collectively as Empowering Leadership factors prove a synergic effect and increase the overall Employee Creativity. The Structural Equation Modeling (SEM) were used for developing theoretical and analyzing data. The result indicates that Empowering Leadership as a main exogenous variable influence Intrinsic Motivation, and Intrinsic Motivation intermediaries Empowering Leadership and Employee Creativity. The alternative policy should be organized clearly about the Employee Creativity. Therefore, both managers and employees must collaborate effectively and communicate the requisite for Creativity. Keywords: Empowering Leadership, Intrinsic Motivation, Employee Creativity. Structural Equation Modeling.